2007 Presidential Address of the CHA: Public History and its Discontents or History in the Age of Wikipedia - Conrad, Margaret (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractIn keeping with the Congress theme of “Bridging Communities: Making Public Knowledge, Making Knowledge Public,” this paper reflects on issues relating to public history and the impact of the Internet — that most public of media — on the ways in which academic historians create and disseminate knowledge. It explores the rise of public history as a profession and field of study over the past three decades, the efforts of the Canadian Historical Association (CHA) since its founding in 1922 to reach a broader public, and the impact of the Internet on the work of professional historians. By raising questions about the role of academic historians in general and of the CHA in particular in bridging what on the surface seems to be the divergent interests of academic and public history, it contributes to a larger discussion that will almost certainly preoccupy CHA presidents for the foreseeable future: where academic history and the arts disciplines generally fit into the postmodern university and into the rapidly expanding world of knowledge fuelled by the Internet and its related technologies.